Longitudinal profile monitors using Coherent Smith-Purcell radiation - Andrews, H; Taheri, F; Barros, J; Bartolini, R; Cassinari, L; Clarke, C; Le Corre, S; Delerue, N; Doucas, G; Fuster-Martinez, N; Konoplev, I; Labat, M; et al. (2014)
Coherent Smith-Purcell radiation has the potential of providing information on the longitudinal profile of an electron bunch. The E-203 experiment at the FACET User Facility measures bunch profiles from the SLAC linac in the hundreds of femtoseconds range and the SPESO collaboration at Synchrotron SOLEIL is planning to make an accurate 2D map of the Coherent Smith-Purcell Radiation emission. © 2013 Elsevier B.V.